2022
DOI: 10.35957/prmm.v3i2.2316
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Motivasi, Persepsi, Kepercayaan Dan E-Wom Terhadap Keputusan Pembelian Layanan Netflix Di Kota Palembang

Abstract: Penelitian ini bertujuan untuk meneliti pengaruh motivasi, persepsi, kepercayaan dan E-WOM terhadap keputusan pembelian layanan netflix di kota palembang. Netflix merupakan salah satu layanan film/drama streaming yang masuk di indonesia sejak tahun 2016 dan pengguna netflix terus bertambah. Sampel yang digunakan dalam penelitian ini adalah 160 dengan menggunakan teknik non purposive sampling dengan kriteria pernah membeli layanan netflix dan bertempat tinggal di kota Palembang. Dalam penelitian ini, menggunaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
1
0
2
Order By: Relevance
“…Based on the result perception of streaming users at Faculty of Economics and Business has no significant effect on purchase decisions, it means that student of Faculty of Economics and Business Unsrat doesn't use their perception to use Netflix. The results of this study are supported by research conducted Fandi and Juwita (2022) which found that perception had no partial effect on purchase decisions. However, this study contradicts the results of research from Lomboan, Saerang and Pangemanan (2013) which found that perception have a significant effect on purchasing decisions.…”
Section: The Influence Of Perception On Consumer Purchase Decisionssupporting
confidence: 77%
See 1 more Smart Citation
“…Based on the result perception of streaming users at Faculty of Economics and Business has no significant effect on purchase decisions, it means that student of Faculty of Economics and Business Unsrat doesn't use their perception to use Netflix. The results of this study are supported by research conducted Fandi and Juwita (2022) which found that perception had no partial effect on purchase decisions. However, this study contradicts the results of research from Lomboan, Saerang and Pangemanan (2013) which found that perception have a significant effect on purchasing decisions.…”
Section: The Influence Of Perception On Consumer Purchase Decisionssupporting
confidence: 77%
“…The results of the study show that simultaneously, social variables, personal and psychological significant and positive influence on decisions purchase, which is indicated by the significant value of the F test < the sig value is 0.000 < 0.05. And partially influential social, personal and psychological variables significant and positive impact on purchasing decisions, which is indicated by value the significance of the t test for each variable < sig value is 0.000 < 0.05 Fandi and Juwita (2022) analyzed the effect of motivation, perception, trust and E-WOM on purchasing decisions for Netflix services in the city of Palembang. Netflix is a streaming film/drama service that has entered Indonesia since 2016 and Netflix users continue to grow.…”
Section: Previous Researchmentioning
confidence: 99%
“…Kepercayaan merupakan subuah kunci utama dalam menjalin hubungan antara satu pihak ke pihak yang lain, agar mendapatkan hubungan yang saling menguntungkan [4]. Memahami kepercayaan dalam konteks bisnis-ke-konsumen menempatkan penekanan lebih besar pada sikap individu terkait kepercayaan konsumen terhadap kualitas dan keandalan layanan [5].…”
Section: Gambar 1 Transaksi Fintech DI Indonesiaunclassified
“…Kepercayaan merupakan sebuah harapan yang dipegang oleh individu atau kelompok saat perkataan, janji, pernyataan lisan atau tulisan dari individu atau kelompok lainnya dapat diwujudkan [4]. Kini, lebih dari sebelumnya, Alfamart berusaha mendapatkan kepercayaan konsumennya melalui aplikasi Alfagift dengan melakukan hal-hal seperti menyelesaikan pesanan dengan cepat, menyediakan barang yang sesuai, dan menjawab pertanyaan sesegera mungkin.Pengalaman konsumen adalah jumlah dari semua sentimen yang dirasakan pelanggan saat berurusan dengan barang atau jasa perusahaan, terlepas dari apakah perasaan itu menyenangkan atau buruk.…”
Section: Universitas Multi Data Palembang | 377unclassified